Implementation of Minimum Service Standards in Health Services for People Suspective of Tuberculosis (Tb) in Labuhanbatu District - Azmi, Hasrul; Kusmanto, Heri; Zulkifli3, Zulkifli (East Asian Journal of Multidisciplinary Research, 2025)
With 824,000 cases and 93,000 fatalities annually, or 11 deaths per hour, Indonesia has one of the third-highest TB burdens in the world, after China and India, according to the WHO Global TB Report 2021. There are still up to 500,000 individuals who have not received treatment and are at danger of spreading the disease since only 49% of Indonesia's estimated 824,000 TB patients were identified and treated. The purpose of this study is to examine how Minimum Service Standards (SPM) are applied in the health care program for individuals suspected of having tuberculosis (TB) in Labuhanbatu Regency. Additionally, it seeks to determine the factors that facilitate and hinder the implementation of SPM policies in the health care program for TB suspects in Labuhanbatu Regency. Qualitative approaches are used in this study. Interviews were used to gather the data, and data triangulation methods were used to assess the data's validity. The research results show that (1) The implementation of the SPM-BK policy for people suspected of TB in Labuhanbatu Regency has not run optimally. In the resource variable, there are limited human resources in the ability to record and report data online (SITB).